What is the optimal time to initiate hypomethylating agents (HMAs) in higher risk myelodysplastic syndromes (MDSs)?. Issue 11 (19th September 2021) - Komrokji, Rami; Al Ali, Najla; Padron, Eric; Lancet, Jeffrey; Nazha, Aziz; Steensma, David; DeZern, Amy; Roboz, Gail; Garcia-Manero, Guillermo; Sekeres, Mikkael A.; Sallman, David
Abstract: Hypomethylating agents (HMAs) are the standard of care for higher risk MDS (HR-MDS) patients. The current dogma is to begin HMA therapy in all HR-MDS patients at the time of initial diagnosis. We investigated the impact of the timing of HMA initiation among HR-MDS patients presenting with adequate blood counts to discern the possible benefit of early treatment based solely on disease risk. We identified 320 HR-MDS patients with adequate hematopoiesis who were treated with HMA. The complete response rates were 21%, 26%, 23%, and 7% respectively for patients treated within 30, 31–60, 61–90, and more than 90 days from time of diagnosis ( p =.046). The median OS from the date of diagnosis was 641, 550, 979, and 806 days, respectively ( p =.2). A delay in initiating HMA therapy in HR-MDS patients with adequate blood counts is not associated with worsened outcomes.